2009
DOI: 10.3102/0034654309341374
|View full text |Cite
|
Sign up to set email alerts
|

Effective Reading Programs for the Elementary Grades: A Best-Evidence Synthesis

Abstract: This article systematically reviews research on the achievement outcomes of four types of approaches to improving the reading success of children in the elementary grades: reading curricula, instructional technology, instructional process programs, and combinations of curricula and instructional process. Study inclusion criteria included use of randomized or matched control groups, a study duration of at least 12 weeks, valid achievement measures independent of the experimental treatments, and a final assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(182 citation statements)
references
References 76 publications
7
156
1
9
Order By: Relevance
“…El caso es que estudios (algunos de ellos experimentales) desarrollados en otros contextos (principalmente anglosajones) tienden a atribuir al trabajo cooperativo en el aula impactos significativos positivos sobre el progreso educativo del conjunto de los alumnos en las distintas etapas educativas y materias curriculares. Así lo recogen revisiones sistemáticas de especial relevancia en la materia (Slavin, Cheung, Groff, & Lake, 2008;Slavin, Lake, Chambers, Cheung, & Davis, 2009;Slavin, Lake, & Groff, 2009). Estas mismas revisiones coinciden en concluir que el aprendizaje cooperativo, para ser efectivo, debe formar parte de una estrategia global bien diseñada, en la que el conjunto de tareas, funciones y recursos que se movilizan disponen de una intencionalidad pedagógica planificada.…”
Section: Aprendizaje Cooperativounclassified
“…El caso es que estudios (algunos de ellos experimentales) desarrollados en otros contextos (principalmente anglosajones) tienden a atribuir al trabajo cooperativo en el aula impactos significativos positivos sobre el progreso educativo del conjunto de los alumnos en las distintas etapas educativas y materias curriculares. Así lo recogen revisiones sistemáticas de especial relevancia en la materia (Slavin, Cheung, Groff, & Lake, 2008;Slavin, Lake, Chambers, Cheung, & Davis, 2009;Slavin, Lake, & Groff, 2009). Estas mismas revisiones coinciden en concluir que el aprendizaje cooperativo, para ser efectivo, debe formar parte de una estrategia global bien diseñada, en la que el conjunto de tareas, funciones y recursos que se movilizan disponen de una intencionalidad pedagógica planificada.…”
Section: Aprendizaje Cooperativounclassified
“…More than 40 empirical studies have shown positive effects of SFA on a variety of measures of student attainment (Quint et al, 2013;Slavin et al, 2009b;Slavin, Lake, Davis, & Madden, 2011). The cumulative evidence from these studies shows positive effects of SFA on a variety of measures of student achievement, as well as on assignments to special education, retentions, and other outcomes (Borman, Hewes, Overman, & Brown, 2003).…”
Section: Previous Research On Sfamentioning
confidence: 99%
“…However, placing strategies as the central foci, without attention to content, has meant that in some classrooms at least instruction remains insular, with little evidence of transfer of reading As we begin supporting the school staff to rework the whole school literacy program, our position is that for students from culturally diverse or marginalized backgrounds, content matters in crucial ways. In a recent reanalysis of achievement test score impacts of comprehension programs, Slavin and colleagues (Slavin, Lake, Chambers, Cheung, & Davis, 2009) noted improved test score effects of comprehensionbased curriculum and instruction. Yet we need to cautiously scrutinize the logic of policy applications of such analyses (Luke, Green, & Kelly, 2010).…”
Section: Work In Progress: Whole School Elementary School Literacy Cumentioning
confidence: 99%